Disrupted harvests: how Ukraine – Russia war influences global food systems – a systematic review - Hamid El Bilali (15864930) (2024)
Amid Ukraine’s geopolitical turmoil, a ripple effect is echoing across global agricultural and food systems – a phenomenon with far-reaching implications for producers, traders, and consumers across the globe. This systematic study delves into this intricate interaction, examining scholarly literature to determine the magnitude and complexities of the war’s impact on global agri-food systems. Utilizing a rigourous methodology, we screened 236 articles from the Web of Science database as of March 2023, narrowing the corpus to 62 significant publications that meet comprehensive eligibility criteria. The war affected all food security dimensions, but the most dramatic impact was on food access. Indeed, the decrease in domestic food production and productivity; the damage to production assets, food production, and food stocks; the increase in production input prices; changes in land use and land degradation; and labour shortage in rural areas reduced food supply and availability, especially that of cereals. The decrease in food availability led to increased food prices and inflation, which, combined with the disruption of agri-food trade, markets, and supply chains, affected food access, especially for the poor and vulnerable people and groups. Effects on food utilization are mainly seen in the decrease in diet quality and dietary diversity. The war also affected the stability dimension, mainly owing to the volatility of food prices and the uncertainty of the future food supply. Similarly, the war has affected all the dimensions of food system sustainability (viz. environmental, social, economic, political). However, some phenomena have particularly affected the socio-economic dimension, such as food insecurity and malnutrition, poverty and vulnerability, and migration and displacement. Therefore, it is imperative to use evidence-based strategies and policies that are not only efficient and effective but also sustainable. Consequently, conducting extensive research into the conflict’s medium- and long-term consequences is crucial, especially in the context of developing countries, which have hitherto been largely overlooked in prior research. Other Information Published in: Policy Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01442872.2024.2329587